Optimized synthesis and characterization of laterite biochar composite for arsenic removal: examining colloidal stability and As(III) oxidation - Prashant Singh; Abhijit Maiti (Biochar)
Abstract Arsenic contamination of water and soil affects many regions worldwide, and an eco-friendly and sustainable decontamination solution is needed. A promising approach involves preparing a composite adsorbent using biochar and laterite-based adsorbent. The biochar composite (LBC) uses biochar as a stable carbon matrix that distributes treated laterite minerals efficiently and reduces agglomeration. In contrast, treated laterite, rich in mixed metal oxides like iron and aluminum hydroxides, enhances the adsorption capacity, selectivity, and stability of biochar. Process optimization determines the optimal pyrolysis temperature, organic–inorganic content, treatment methodology, biochar incorporation at a particular pH, and colloidal instability. The Langmuir isotherm model estimates maximum arsenic adsorption capacities of 21 g kg–1 for As(V) and 14 g kg–1 for As(III), respectively, with high adsorption rates at both low and high arsenic concentrations. FTIR and XPS analysis suggest hydroxyl and metal oxide aid adsorption, while the quenching experiments with EPR analysis confirm the active role of hydroxyl-free radicles in the oxidation and subsequent adsorption of arsenic species. The used adsorbent can be regenerated using 0.2 M NaOH and shows a safe landfilling option for spent adsorbent based on the TCLP tests. The synergistic combination of laterite with biochar makes LBC an efficient and sustainable solution for the removal of arsenic from water with high adsorption capacity and easy regeneration. Graphical Abstract